Indapamide retard as the medication of choice in elderly patients with arterial hypertension - I. I. Chukaeva; Ya. G. Spiryakina (Российский кардиологический журнал)
The modern society faces a steady increase in the numbers of elderly people, which is associated with a range of social and medical problems. Age-related aspects of body anatomy and physiology, multiple comorbidity, and cognitive decline restrict the choice of medications in elderly patients. The paper discusses the need for the agreement between the choice of antihypertensive agents in elderly patients and the importance of organoprotection. From the evidence-based medicine standpoint, indapamide retard is considered as the medication which meets all the requirements for arterial hypertension treatment in elderly patients.